Persistence and proliferation of a Chinese Metarhizium anisopliae s.s. isolate in the peanut plant root zone. Issue 6 (2nd June 2016) - Liu, Xun; Nong, Xiangqun; Wang, Qinglei; Li, Xingjia; Wang, Guangjun; Cao, Guangchun; Zhang, Zehua
ABSTRACT: We evaluated the persistence and proliferation of a Chinese Metarhizium anisopliae s.s. isolate (M202-1) at different distances from peanut roots during peanut development. The results showed that the duration, distance from root and depth resulted in significant effects and interactions on the survival of the fungus. The fungal population showed a rapid early decline, followed by a gradual stabilisation or a slight re-establishment. The rhizospheric population declined by 50% within 21 d, faster than other population away from the root. The decline reached the lowest level between days 60 and 90, with levels of 10.8–24.7% of the initial inoculum. In comparison, the rhizospheric population re-established earliest and increased to 52.9% of the initial on day 150. The 3–5-cm shallow layer was more suitable than the 13–15-cm layer for fungal persistence. When Metarhizium was applied outside the 11.5-cm radius around the root, it would diffuse inward in 30 d, causing a significant increase at the rhizosphere on day 90. In accordance with the sampling date corresponding to the root development stage, the results suggest that the rhizosphere of peanut middle–later development was conducive to Metarhizium proliferation, promoting Metarhizium application for pest control in the soil.